The Right to be Heard Prior to Judicial Proceedings: Human Rights and Fair Trial Deficiencies in Indonesian Pre-Trial Processes - Erwin Susilo; Mohd. Din; Suhaimi Suhaimi; Teuku Muttaqin Mansur (Yustisia, 2026)
The Protection from arbitrary detention is an essential component of a democratic judicial system and a core element of the right to a fair trial. However, in Indonesia, the previous and the newly passed Criminal Procedure Code (KUHAP) do not expressly require detained suspects to be presented before a judge during the pre-trial procedures. This circumstance raises questions about the effectiveness of judicial oversight over coercive methods and the realisation of procedural rights protected under human rights standards. The problem is of particular relevance, as the Indonesian pre-trial process serves a similar purpose to habeas corpus in many countries, which necessitates the detainee’s personal appearance before the court. This article employs normative legal research using statutory, conceptual, and comparative approaches. Comparative analysis is conducted by examining habeas corpus regulations and judicial oversight mechanisms in England, the United States, India, the Philippines, Spain, Portugal, and the Netherlands. The analysis demonstrates that the absence of an obligation to present detained suspects before a judge weakens procedural fairness, limits the suspect’s opportunity to be heard directly, and reduces the effectiveness of judicial supervision over detention. To address these shortcomings, reform of the KUHAP should provide an explicit requirement for the presentation of detained suspects in pretrial hearings and strengthen the active supervisory role of judges as a safeguard against arbitrary deprivation of liberty